**Chapter 8 Algebraic Expressions and Operations on them Set 8.3**

Question 1.

Subtract the second expression from the first.

i. (4xy – 9z); (3xy – 16z)

ii. (5x + 4y + 7z); (x + 2y + 3z)

iii. (14x² + 8xy + 3y²); (26x² – 8xy – 17y²)

iv. (6x² + 7xy + 16y²); (16x² – 17xy)

v. (4x + 16z); (19y – 14z + 16x)

Solution:

i. (4xy – 9z) – (3xy – 16z)

= 4xy – 9z – 3xy + 16z

= (4xy – 3xy) + (16z – 9z)

= xy + 7z

ii. (5x + 4y + 7z) – (x + 2y + 3z)

= 5x + 4y + 7z – x – 2y – 3z

= (5x – x) + (4y – 2y) + (7z – 3z)

= 4x + 2y + 4z

iii. (14x² + 8xy + 3y²) – (26x² – 8xy – 17y²)

= 14x² + 8xy + 3y² – 26x² + 8xy + 17y²

= (14x² – 26x²) + (8xy + 8xy) + (3y² + 17y²)

= -12x² + 16xy + 20y²

iv. (6x² + 7xy + 16y²) – (16x² – 17xy)

= 6x² + 7xy + 16y² – 16x² + 17xy

= (6x² – 16x²) + (7xy + 17xy) + 16y²

= -10x² + 24xy + 16y²

v. (4x + 16z) – (19y— 14z + 16x)

= 4x + 16z – 19y + 14z – 16x

= (4x – 16x) – 19y + (16z + 14z)

= -12x – 19y + 30z